2018
DOI: 10.1002/jcb.27094
|View full text |Cite
|
Sign up to set email alerts
|

Small‐molecule–based generation of functional cardiomyocytes from human umbilical cord–derived induced pluripotent stem cells

Abstract: The purpose of this study was to investigate the cardiac‐differentiation potential of induced pluripotent stem cells (iPSCs) generated from human umbilical cord–derived mesenchymal cells. Spontaneous beating colonies were observed at day 7 after the sequential addition of CHIR99021 and IWP‐4. The combined use of CHIR99021 and IWP‐4 downregulated the expression of pluripotency markers while upregulating cardiac transcription factors and cardiomyocyte‐specific markers. The derived cardiomyocytes demonstrated typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For printing vascular channels, human umbilical vein endothelial cells were obtained from Lonza (U.S.A) and were cultured in EBM‐2 supplemented with 1% v/v penicillin‐streptomycin. The hiPSC cell line referred to as Cellartis Human iPS Cell Line 12 (ChiPSC12) (Takara Bio, USA) was differentiated into cardiomyocytes (hiPSC‐CMs) using a previously published protocol through the use of small molecules (CHIR99021 and Wnt‐C59) . Human iPSC‐derived cardiac spheroids (hiPSC‐CSs) were shipped from the University of Hong Kong.…”
Section: Methodsmentioning
confidence: 99%
“…For printing vascular channels, human umbilical vein endothelial cells were obtained from Lonza (U.S.A) and were cultured in EBM‐2 supplemented with 1% v/v penicillin‐streptomycin. The hiPSC cell line referred to as Cellartis Human iPS Cell Line 12 (ChiPSC12) (Takara Bio, USA) was differentiated into cardiomyocytes (hiPSC‐CMs) using a previously published protocol through the use of small molecules (CHIR99021 and Wnt‐C59) . Human iPSC‐derived cardiac spheroids (hiPSC‐CSs) were shipped from the University of Hong Kong.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported that the inhibition of Wnt pathway promotes the differentiation of stem cells toward cardiomyocytes. Inhibitor Wnt production-4 (IWP-4) was also reported to produce functional cardiomyocytes from induced pluripotent stem cells and embryonic stem cells[ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hUCMSCs derived from discarded tissue of newborns are rich in sources. hUCMSCs also exhibit high proliferative capability, low immunogenicity, and multilineage differentiation potential [ 9 11 ]. However, whether hUCMSCs can be applied in breast tissue engineering has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%